PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT CITRA LENTERA INDONESIA - Djalkhoir, Nurkholis; Azis, Abdul (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of training and work motivation on employee performance at PT Citra Lentera Indonesia. This research used a quantitative method with a sampling technique using saturated sampling and obtained a sample of 65 respondents. The analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the results of the calculated t hypothesis test of 7,123 > t table 2.002 with a probability value (sig) of 0.000 < 0.05, it can be concluded that partially training has a positive and significant influence on employee performance at PT Citra Lentera Indonesia. The results of research based on the multiple linear regression equation show that the regression equation is, Y = 2990 + 0,851 X1 + 0,652 X2. Based on the results of the hypothesis test t count 3,752 > t table 2.002 with a probability value of 0.000 < 0.05, it can be concluded that partially work motivation has a positive and significant influence on employee performance at PT Citra Lentera Indonesia. Based on the results of hypothesis testing with a calculated f value of 46,509 > f table 3.159 with a probability value (sig) of 0.000 < 0.05, The R-Square value of 0,600 indicates that training and work motivation have an influence on employee performance by 60,0%, while the rest influenced by other variables.